Asian elephant movement ecology within human-elephant conflict landscape in Johor, peninsular Malaysia - Kaliyappan, Gukaaneswaran (2024)
As the largest terrestrial animal on earth, elephants perform important and irreplaceable ecological roles within their natural ecosystems. However, elephants are regarded as pests owing to significant damages they can cause to farms. Farmers find elephants extremely difficult to manage due to elephants’ vast appetite, high degree of intelligence to circumvent mitigating efforts, and potential for causing harm. In Malaysia, movement ecology of wildlife is challenging to be incorporated into conservation actions due to lack of direct sightings in the rainforest and difficulty to deploy tracking devices on endangered species. However, the growing database of Asian elephant (Elephas maximus) GPS movement in Malaysia provides opportunities for researchers to elucidate the movement ecology and spatial needs of Asian elephant that can benefit both conservation and management in a variety of ways (e.g., mitigation measures). This study aims to help the agriculture community to manage Human-Elephant Conflict in Johor, Malaysia and promote coexistence with elephants. The objectives of this study are to estimate the home range sizes of collared elephants in Johor using dynamic Brownian Bridge Movement Models and, to determine the impact of land use changes on elephant movement pattern using spatial and pathway analysis. We analysed GPS telemetry data from eight elephant individuals in Johor between 2020 – 2022, and found the elephants to have large area requirements, with mean home ranges (95% utilization) of 245 km² (min-max range 142 km² – 326 km²). The home range sizes were smaller when the proportion of agricultural land used within its home range was higher (R2 = 0.56, p-value = 0.033, F1,6 = 7.58) and when the proportion of forest within its home range was smaller (R2 = 0.59, p-value = 0.027, F1,6 = 8.52). Least-cost path and Circuitscape analyses of possible corridors connecting the core area (50% utilization home range) were used to visualized landscape connectivity and help informed potential sites for the development of corridors in future. This thesis contributes to a better understanding of Asian elephant movements and space use within agricultural and forested landscapes, and help support conservation management of Asian elephants and their habitat.